2017
DOI: 10.1371/journal.pone.0185825
|View full text |Cite|
|
Sign up to set email alerts
|

Gait parameters are differently affected by concurrent smartphone-based activities with scaled levels of cognitive effort

Abstract: The widespread and pervasive use of smartphones for sending messages, calling, and entertainment purposes, mainly among young adults, is often accompanied by the concurrent execution of other tasks. Recent studies have analyzed how texting, reading or calling while walking–in some specific conditions–might significantly influence gait parameters. The aim of this study is to examine the effect of different smartphone activities on walking, evaluating the variations of several gait parameters. 10 young healthy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
2
22
0
1
Order By: Relevance
“…A recent narrative review of 20 studies, mostly in young healthy adults, concluded that texting was associated with impaired gait performance [10]. Subsequent studies have also shown consistent findings; however, studies continue to be conducted in young adults [11][12][13], or with small sample sizes of as few as 10 participants [12][13][14][15]. Given the increasing use of smartphones and other devices in older age groups [16], the higher dual-task cost of similar activities in older versus younger adults, and the evidence of increasing "pedestrian distraction by technology" [17], there is a need to investigate the impact of texting on walking across age categories.…”
Section: Introductionmentioning
confidence: 99%
“…A recent narrative review of 20 studies, mostly in young healthy adults, concluded that texting was associated with impaired gait performance [10]. Subsequent studies have also shown consistent findings; however, studies continue to be conducted in young adults [11][12][13], or with small sample sizes of as few as 10 participants [12][13][14][15]. Given the increasing use of smartphones and other devices in older age groups [16], the higher dual-task cost of similar activities in older versus younger adults, and the evidence of increasing "pedestrian distraction by technology" [17], there is a need to investigate the impact of texting on walking across age categories.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, using a cell phone while walking reduces the ability of a pedestrian to avoid an obstacle and increases the variability in response. Most previous studies have assumed it is some cognitive demand of texting on a cell phone that leads to increased risk of accidents etc 11,15,16,24 . Our findings, however, suggest the opposite: that it is instead a combination of simply looking at the phone (i.e., “inattentional blindness” 9,10 ) and the complexity of the decisions that need to be made with respect to events going on in the environment (i.e., obstacle avoidance) that increase the risk for collision and potential injury.…”
Section: Discussionmentioning
confidence: 99%
“…These gait changes are consistent with using more “cautious” walking strategies while using a cell phone 11,15,16 , possibly to improve dynamic stability 14,16,23 . These effects may scale with either increasing cognitive difficulty of the cell phone task 24 or increased physical difficulty of the walking task 25 . However, most gait changes can be attributed to walking slower and altering body posture to handle the phone 26 and may possibly even disappear over time with adaptation to the task 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The Bayes factor for the average RPE in the self-paced exercise was BF10 = 0.720, which indicate an anecdotal evidence in favor of the null hypothesis indicating the absence of effect between low and high load conditions. The average RPE for both conditions were: 14 The Bayes factor for the normalized VAS score after the self-paced exercise was BF10 = 0.588. The Bayes factor supports the null hypothesis and yield anecdotal evidence in favor of the null hypothesis.…”
Section: Performancementioning
confidence: 99%
“…However, other authors have questioned that metabolic resources are a limiting factor and they indicate that the impairment might be rather due to the attentional limitations when perform both tasks [12,13]. Nonetheless, there is evidence showing that concurrent exercise (which might tap the same underlying cognitive processes) can impair cognitive performance compared to when the cognitive a task is performed alone [14][15][16]. For instance, Epling et al [17] found a decrement in the number of words recalled when participants completed a 5 min self-paced (outdoor) running exercise.…”
Section: Introductionmentioning
confidence: 99%